Environmental management tool kit for obsolete pesticides. (2009)
Stocks of obsolete, unwanted and banned pesticides continue to represent a serious public health and environmental threat, particularly in developing countries. This tool kit has been developed for country project managers, officers of government ministries of agriculture, environment and health, and regional and district officers and storekeepers, to support them in planning all the steps of a safe disposal program.--Publisher's description
Keywords: Pesticide waste; Pesticides; Pesticides -- Environmental aspects